Yellow Garden Spider, Writing Spider Argiope aurantia (Lucas) (Arachnida: Araneae: Araneidae) - Taryn B. Griffith; Jennifer Lynn Gillett-Kaufman (EDIS)
Most commonly known as the yellow garden spider, Argiope aurantia Lucas is a large orb-weaving spider. It is also known as the writing spider due to the trademark vertical zig zag pattern they construct in their webs (Enders 1973). The yellow garden spider is a very common species and has captured many gardener’s attention due to their zig zag web, striking black and white pattern, and relatively large size. Although their appearance may cause alarm, the species is relatively harmless and will generally leave its web to flee rather than attack when disturbed (Enders 1973). https://edis.ifas.ufl.edu/in1273